Similar Mortality Among United States Veterans With Invasive and Noninvasive Pneumonia due to Group B Streptococcus. (2nd February 2022) - Banks, Richard E; Wilson, Brigid M; Bej, Taissa; Briggs, Janet M; Song, Sunah; Goto, Michihiko; Jump, Robin L P; Perez, Federico
Abstract: Background: The nosology of noninvasive pneumonia due to group B Streptococcus (GBS) is not well defined. This study compared clinical characteristics and outcomes of patients with invasive pneumonia and noninvasive pneumonia caused by GBS. Methods: We conducted a retrospective cohort study among Veterans Affairs (VA) healthcare users between 2008 and 2017. Using data from electronic health records, we identified patients who had blood or respiratory cultures that grew GBS and had invasive pneumonia or noninvasive pneumonia. We analyzed patient and infection characteristics associated with all-cause mortality, including among the subset of patients with cultures that were monomicrobial for GBS. Results: Among 1791 patients with GBS pneumonia, 646 (36%) cases were invasive and 1145 (64%) were noninvasive. Among those, 535 and 424 cases of invasive and noninvasive pneumonia, respectively, had cultures that were monomicrobial for GBS. All-cause 30-day mortality among those with monomicrobial GBS pneumonia was 15% for both those with invasive and noninvasive disease, respectively. Increasing age, severity of illness, healthcare exposure in the previous 90 days, and polymicrobial infection with Staphylococcus aureus were independently associated with all-cause mortality at 30 days. Conclusions: In this large cohort, even when considering cases for which GBS was the only pathogen recovered, >40% of GBS pneumonia cases were noninvasive. All-cause mortality was comparable for invasive and noninvasive pneumonia. These findings suggest that the burden of GBS pneumonia may be greater than previously recognized by surveillance of invasive GBS disease and may inform treatment and prevention efforts. Abstract : In a large cohort of US Veterans, noninvasive group B Streptococcus (GBS) pneumonia occurred at a comparable incidence and was associated with similar mortality (even when focusing on monomicrobial cases) compared to invasive GBS pneumonia, suggesting an underestimation of the burden of GBS pneumonia.